2011
DOI: 10.1002/jcp.22589
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of CITED2 using short‐hairpin RNA sensitizes cancer cells to cisplatin through stabilization of p53 and enhancement of p53‐dependent apoptosis

Abstract: CITED2 is a transcriptional modulator which has been implicated in human oncogenesis. In the present study, we examined whether CITED2 is also involved in the resistance of cancer cells to the chemotherapeutic drug cisplatin. We first observed that knockdown of CITED2 using short-hairpin RNA sensitized non-tumorigenic HEK293 cells to cisplatin. Sensitization to cisplatin following knockdown of CITED2 was also observed in cervical carcinoma HeLa cells and in cisplatin-resistant HeLa cells, thereby showing that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 39 publications
1
33
2
Order By: Relevance
“…We demonstrated that Introduction 47 Hypoxia inducible factors (HIF) 1 1 and 2 are crucial to mediate 48 the cellular adaptation in response to hypoxia [1]. HIF-1 and HIF-2 49 are heterodimers formed by the oxygen-sensitive subunits, HIF-1a 50 and HIF-2a, and a constitutive subunit referred to as HIF-1b or 51 Arnt1. Under normoxic conditions, the oxygen, 2-oxoglutarate and 52 iron-dependent prolyl hydroxylases (PHDs) catalyse the hydroxyla- 53 tion of two key proline residues present in the oxygen-dependent 54 degradation domain (ODDD) of HIF-1a and HIF-2a, promoting their 55 recognition by the von Hippel-Lindau protein (pVHL) E3 ligase and 56 their subsequent degradation by the proteasome [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that Introduction 47 Hypoxia inducible factors (HIF) 1 1 and 2 are crucial to mediate 48 the cellular adaptation in response to hypoxia [1]. HIF-1 and HIF-2 49 are heterodimers formed by the oxygen-sensitive subunits, HIF-1a 50 and HIF-2a, and a constitutive subunit referred to as HIF-1b or 51 Arnt1. Under normoxic conditions, the oxygen, 2-oxoglutarate and 52 iron-dependent prolyl hydroxylases (PHDs) catalyse the hydroxyla- 53 tion of two key proline residues present in the oxygen-dependent 54 degradation domain (ODDD) of HIF-1a and HIF-2a, promoting their 55 recognition by the von Hippel-Lindau protein (pVHL) E3 ligase and 56 their subsequent degradation by the proteasome [2].…”
mentioning
confidence: 99%
“…665 Of particular interest, yeast two-hybrid screenings have pointed 666 out a potential interaction between FBXL5 and p300 in the human 667 liver protein network [47]. tion might also indirectly affect the acetylation process of tran-683 scription factors by CBP/p300, such as p53 and NF-jB [49,50]. 684 Since cellular iron and oxygen deprivation destabilizes FBXL5 and 685 promotes its own degradation by the proteasome [27,28], the 686 interaction between CITED2 and the CH1 domain of CBP/p300 687 might also be modulated by the cellular availability of iron and 688 oxygen.…”
mentioning
confidence: 99%
“…In addition, Haps59 may be activated by another binding partner of the promiscuous CH1 domain which is present in 293 cells. The CH1 domain is known to interact with many oncogenes including p53 [35],[36],[37], CITED2 [28],[38],[39],[40], NF-κB-p65 [41],[42], Stat-2 [43],[44], Pit-1 [45],[46],[47], and HNF-4 [48],[49]. One possibility is that activation of Haps59 in Flp-In 293 cells is caused by the interaction between the CH1 domain and the adenovirus E1A protein [50].…”
Section: Resultsmentioning
confidence: 99%
“…The wild-type p53 protein is able to exert a range of anti-proliferative effects, including the induction of apoptosis and causing a marked increase in the sensitivity of these cells to DDP (18,19). However malignancies with mutated p53 genes and aberrant p53 proteins in laboratory studies and one clinical study have been observed to be less responsive to chemotherapy agents that induce DNA damage, such as DDP (20,21).…”
Section: Discussionmentioning
confidence: 99%